Experimental Study For Heat Transfer Enhancement of a Radiator using Twisted Inserts with Different Coolants - khan, Farukh; Yunus, Vakar (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
The radiator is used for cooling the internal combustion engine cylinder with the help of different coolant fluids. It is an essential part for any IC engine for its proper and smooth operation. In radiator the coolant fluid absorb the heat from engine cylinder and finally rejects to surrounding air. It has been observed by various researchers that the enhancement of thermal performance of a radiator is a major problem. In this dissertation study of a car radiator is investigated to improve its thermal performance by increasing heat transfer rate. In present work the experimental work of three cases have been investigated for various mass flow rate for general heat exchange fluid of water and coolant with mixture (50% of ethylene glycol + 50%water).We have considered firstly by simple circular tube radiator and secondly the twisted wire inserted radiator and thirdly twisted tape inserted radiator for its experimental observation and performance by using two fluids as water and mixture (50% of ethylene glycol +50% of water).In this project work the Nusselt number and heat transfer coefficient and heat transfer have been calculated experimentally and then co- related with the available co-relation Dittuss-boelter’s and Gnielinski. The first experiments have been done by using Coolant (water).It has seen that the 33.33% enhancement of Nusselt number and 40% enhancement of heat transfer by using twisted inserts in simple tube of radiator as compared to simple tube of in radiator at different mass flow rates. The second experiments have been done by using a coolant (with mixture of ethylene glycol + water (50:50) combination. So it is a biggest achievement of heat transfer rate in car radiator and better cooling effect and finally reduces spaces in car radiator tubes.